Infective Versus Non-Infective Respiratory Illness Admissions: Comparative cost analysis in a tertiary hospital in Malaysia - Kiran Ganesh Balakrishnan; Mohd Rizal Abdul Manaf; Mohd Rohaizat Hassan; Kamarul Imran Musa; Azizul Rahman Mohamad Jamil (ACHSM, 2024)
Background: Severe Acute Respiratory Infection (SARI) that is mainly caused by the Influenza virus, poses a significant public health threat, demanding timely detection and preventive measures. This study assesses the financial implications of managing two distinct respiratory conditions: SARI and Acute Exacerbation of Bronchial Asthma (AEBA). Method: Data were collected for 100 patients, with 50 cases of SARI and 50 cases of AEBA, admitted to Hospital Canselor Tuanku Muhriz (HCTM) from July to December 2022. Cost analysis was conducted from a provider perspective, considering factors such as building, asset, emolument, overhead, utility, medication, consumables, and laboratory and imaging expenses. Results: The study revealed that the average total cost of treating SARI patients was RM 1,587.11 ($US334.80), significantly higher (30.7%) than AEBA patients at RM 1,214.41 ($US256.18).This was mainly due to the acute and severe nature of SARI, requiring more intensive medical interventions, potentially leading to complications and greater strain on healthcare resources. The study highlighted the economic challenges posed by SARI, provided valuable insights for resource allocation and public health planning. The study's limitations include retrospective data collection and potential underestimation of actual costs due to top-down costing methodology. Conclusion: SARI, especially in the elderly population, leads to substantial healthcare costs and economic impact. Effective preventive measures, such as vaccination, are crucial in reducing the burden of influenza-related illnesses. Health financing plays a vital role in addressing communicable diseases and ensuring the well-being of the population.